Mindfulness Breathing terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Amaliah Mahmudah; Okti Sri Purwanti (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the effectiveness of mindfulness breathing on lowering blood pressure in hypertensive patients. The study used a case study design, providing an evidence-based maintenance intervention in the form of mindfulness breathing relaxation techniques for 5–10 minutes to five hypertensive patients aged 40–65 years, measured using Mean Arterial Pressure (MAP). The results showed that overall, MAP values ​​after the intervention ranged from 88.7–106.7 mmHg, indicating improvements in arterial perfusion pressure in the majority of hypertensive patients. In conclusion, the application of mindfulness breathing relaxation techniques has been proven effective in lowering blood pressure, thus providing a useful non-pharmacological approach to help control blood pressure and support the recovery process.   Keywords: Hypertension, Mindfulness Breathing, Blood Pressure